1998
DOI: 10.1021/ef9800664
|View full text |Cite
|
Sign up to set email alerts
|

Subfractionation and Characterization of Mayan Asphaltene

Abstract: Mayan crude, residuum, and hydrocracked asphaltenes have been separated into two fractions by extended Soxhlet extraction in n-heptane. Although the solubility, composition, and molecular structures differ slightly, the greatest difference between the two asphaltene fractions is the degree to which they associate in solution. The vapor-phase osmometry molecular weight, molecular size by size-exclusion chromatography, and small-angle neutron scattering indicate that approximately 25% of Mayan asphaltene is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
132
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(143 citation statements)
references
References 38 publications
10
132
1
Order By: Relevance
“…The higher capacity of n-pentane for the precipitation of asphaltenes compared with the yield obtained with n-heptane is a common finding reported in the literature [26]. Apparently, the use of higher carbon-number alkane solvents results in lower asphaltene yields and increased levels of resinous materials [26,32]. Similar behavior is observed for oils from different sources that have different API gravities using n-C 5 and n-C 7 for asphaltene precipitation [33], and the results of the present work showed the same behavior: 21.5% versus 15.5% for n-C 5 and n-C 7 asphaltenes, respectively (Fig.…”
Section: Use Of N-alkane Solvents (N-pentane and N-heptane) For Asphamentioning
confidence: 89%
“…The higher capacity of n-pentane for the precipitation of asphaltenes compared with the yield obtained with n-heptane is a common finding reported in the literature [26]. Apparently, the use of higher carbon-number alkane solvents results in lower asphaltene yields and increased levels of resinous materials [26,32]. Similar behavior is observed for oils from different sources that have different API gravities using n-C 5 and n-C 7 for asphaltene precipitation [33], and the results of the present work showed the same behavior: 21.5% versus 15.5% for n-C 5 and n-C 7 asphaltenes, respectively (Fig.…”
Section: Use Of N-alkane Solvents (N-pentane and N-heptane) For Asphamentioning
confidence: 89%
“…It has been found that the yield and properties of asphaltenes precipitated from a crude oil depend on various factors, such as the precipitant, liquid precipitant-to-oil volume ratio, contact time, pressure, and temperature [12][13][14]. Some standard precipitation methods have been developed in laboratory to obtain an accurate and consistent asphaltene content.…”
Section: Introductionmentioning
confidence: 99%
“…[2]. Asphaltenes are petroleum hydrocarbons with extremely complex molecular structure containing sulfur (0.3-10.3%), oxygen (0.3-4.8%), nitrogen (0.6-3.3%), and metal elements, such as Fe, Ni, and V in a small amount [3][4][5][6]. One of the most important problems in oil industries is the precipitation of heavy components of crude oil such as asphaltenes.…”
Section: Introductionmentioning
confidence: 99%